Charity and its social effects - dr.Zainab Sameer Ali (Journal of College of Education, 2025)
All praise is due to Allah, the Lord of the worlds, and may peace and blessings be upon the Master of the Messengers, Muhammad ibn Abdullah, and upon his pure family and chosen companions.Charity (ṣadaqah) is a term that encompasses all acts of righteousness and goodness within society. It is frequently mentioned in both the Quranic verses and noble Prophetic traditions, which reflects its significant role in establishing a sound and healthy society free from the afflictions that may harm it. Emphasizing the benefits and rewards of charity plays a role in encouraging believers who seek the blessings of both this world and the Hereafter.The Prophet Muhammad (peace be upon him) highlighted the importance of charity in every human action. He said:"Every human being is created with three hundred and sixty joints. So whoever declares the greatness of Allah, praises Him, declares His oneness, glorifies Him, seeks His forgiveness, removes a stone, thorn, or bone from the path of people, enjoins good, or forbids evil, in accordance with the number of those joints, then he walks having saved himself from Hellfire." In this research, I discuss the concept of charity both linguistically and in Islamic terminology, its virtues, and how it differs from obligatory almsgiving (ṣadaqah). I also explore its role in spreading social solidarity and the importance of that role in strengthening the structure of Islamic society.